SEMANTIC-STRUCTURAL PECULIARITIES OF SHAKESPEAREAN NEOLOGISMS - Ismoilova Dilorom (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
The article reveals the contributions of William Shakespeare to the development of the English language. Author discusses structural features of  Shakespearean  neologisms and highlights semantic differences in terms of periods of English language. The study reveals the peculiarities of Shakespearean neologisms due to the standpoints of methods of analysis. The article targeted to clarify the neologisms made in the realm of morphological word-formation. The author utilized the observation method and conducted the qualitative research. The neologisms by the dramatist are divided into 4 categories considering their ways of formation. They are following: the neologisms that were coined by affixation; the neologisms that were minted by syntactic  way; originally new-born words; the neologisms that were coined by conversion.